(untitled) (Journal of Ideas in Health, 2020)
Background: Missing outcome data in clinical trials are important determinants of internal validity; however, its burden and risk in gestational diabetes mellitus (GDM) mothers supplemented with vitamin D remain poorly studied. Therefore, a systematic review and meta-analysis protocol is proposed here to study it. Methods: The English language publications, irrespective of its publication date, will be searched in electronic databases for randomized controlled trials studying the above outcome. The eligible trials will undergo the risk of bias assessment by the Cochrane tool. Data on its trial design, population characteristics, interventions compared, and the outcome will be abstracted. The prevalence and incidence (in risk ratio) of missing outcome data will be estimated meta-analytically. The statistical heterogeneity assessment will include the use of Chi2 and I2 statistics. For the explanation of any substantial heterogeneity, a meta-regression analysis will ensue. The statistical significance will be determined at P <0.05 and 95% CI. All analyses will be done in Stata statistical software. If the quantitative analysis is not possible, narrative reporting will happen. Results: The reporting of the review will follow the PRISMA guideline. Statistically significant pairwise meta-analysis finding’s grading will occur by the GRADE approach. Conclusion: The proposed review will estimate the prevalence of missing outcome data in vitamin D supplemented GDM mothers in clinical trials and compare its risk with the placebo recipients. PROSPERO registration ID: CRD42020180634 References • Quintanilla Rodriguez BS, Mahdy H. Gestational Diabetes. [Updated 2019 Dec 23]. StatPearls. Treasure Isl StatPearls Publ. 2020. Available from: https://www.ncbi.nlm.nih.gov/books/NBK545196/ • Committee on Practice Bulletins—Obstetrics. ACOG Practice Bulletin No. 190: Gestational Diabetes Mellitus. Obstet Gynecol. 2018;131: e49–64. Available from: http://www.ncbi.nlm.nih.gov/pubmed/29370047 • Mack LR, Tomich PG. Gestational Diabetes: Diagnosis, Classification, and Clinical Care. Obstet Gynecol Clin North Am [Internet]. 2017; 44:207–17. Available from: http://www.ncbi.nlm.nih.gov/pubmed/28499531 • Coustan DR. Gestational Diabetes Mellitus. Clin Chem. 2013; 59:1310–21. Available from: http://www.clinchem.org/cgi/doi/10.1373/clinchem.2013.203331 • Management of Diabetes in Pregnancy: Standards of Medical Care in Diabetes—2019. Diabetes Care. 2019;42: S165–72. Available from: http://care.diabetesjournals.org/lookup/doi/10.2337/dc19-S014 • Saha S. Compliance and barriers to self-monitoring of blood glucose in patients with gestational diabetes mellitus: A systematic review. Int J Health Sci (Qassim).2019;13:44–52. Available from: http://www.ncbi.nlm.nih.gov/pubmed/31123440 • Akbari M, Mosazadeh M, Lankarani K, Tabrizi R, Samimi M, Karamali M, et al. The effects of vitamin d supplementation on glucose metabolism and lipid profiles in patients with gestational diabetes: a systematic review and meta-analysis of randomized controlled trials. Horm Metab Res.Germany; 2017;49:647–53. Available from: http://www.thieme-connect.de/DOI/DOI?10.1055/s-0043-115225 • Saha S, Saha S. A comparison of the risk of cesarean section in gestational diabetes mellitus patients supplemented antenatally with vitamin D containing supplements versus placebo: A systematic review and meta-analysis of double-blinded randomized controlled trials. J Turkish-German Gynecol Assoc. 2020; 21:201–12. https://dx.doi.org/10.4274%2Fjtgga.galenos.2020.2019.0164 • Saha SS, Saha SS. The risk of morbidities in newborns of antenatal vitamin D supplemented gestational diabetes mellitus patients. Int J Health Sci (Qassim). Qassim University; 2020; 14:3–17. Available from: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7475207/ • Saha S, Saha S. A Comparison of the Changes in Gestational Weight, Body Mass Index, and Serum Vitamin D Level in Gestational Diabetes Mellitus Patients Complemented with Vitamin D in Contrast to Those Who Did Not Receive the Supplement: A Protocol for Systematic Review a. Int J Diabetes Metab. S. Karger AG; 2019; 25:74–9. https://doi.org/10.1159/000505269 • Mavridis D, White IR. Dealing with missing outcome data in meta‐ Res Synth Methods.2020;11:2–13. Available from: https://onlinelibrary.wiley.com/doi/abs/10.1002/jrsm.1349 • Higgins JPT GS (editors). Cochrane Handbook for Systematic Reviews of Interventions Version 5.1.0 [updated March 2011]. Cochrane Collab. 2011 [cited 2020 Aug 27]. Available from: https://training.cochrane.org/handbook/archive/v5.1/ • Asemi Z, Hashemi T, Karamali M, Samimi M, Esmaillzadeh A. Effects of vitamin D supplementation on glucose metabolism, lipid concentrations, inflammation, and oxidative stress in gestational diabetes: a double-blind, randomized controlled clinical trial. Am J Clin Nutr.2013;98:1425–32. https://doi.org/10.3945/ajcn.113.072785 • Asemi Z, Karamali M, Esmaillzadeh A. Effects of calcium–vitamin D co-supplementation on glycaemic control, inflammation and oxidative stress in gestational diabetes: a randomised placebo-controlled trial. Diabetologia .2014;57:1798–806. https://doi.org/10.1007/s00125-014-3293-x • Institute of Medicine (US) Committee to Review Dietary Reference Intakes for Vitamin D and Calcium. Dietary Reference Intakes for Calcium and Vitamin D. Ross AC, Taylor CL, Yaktine AL, Del Valle HB, editors. Washington (DC): National Academies Press (US); 2011. Available from: https://books.google.co.in/books?id=VF2aRQJ6IZ4C • Gossman W, Chauhan K, Huecker MR. Vitamin D. StatPearls. 2019. Available from: http://www.ncbi.nlm.nih.gov/pubmed/28722941 • Curtis EM, Moon RJ, Harvey NC, Cooper C. Maternal vitamin D supplementation during pregnancy. Br Med Bull. 2018; 126:57–77. https://doi.org/10.1093/bmb/ldy010 • Knabl J, Vattai A, Ye Y, Jueckstock J, Hutter S, Kainer F, et al. Role of Placental VDR Expression and Function in Common Late Pregnancy Disorders. I Int J Mol Sci. 2017;18(11):2340. https://doi.org/10.3390/ijms18112340 • Yazdchi R, Gargari BP, Asghari-Jafarabadi M, Sahhaf F. Effects of vitamin D supplementation on metabolic indices and hs-CRP levels in gestational diabetes mellitus patients: a randomized, double-blinded, placebo-controlled clinical trial. Nutr Res Pract. 2016; 10:328. Available from: http://synapse.koreamed.org/DOIx.php?id=10.4162/nrp.2016.10.3.328 • Jamilian M, Samimi M, Ebrahimi FA, Hashemi T, Taghizadeh M, Razavi M, et al. The effects of vitamin D and omega-3 fatty acid co-supplementation on glycemic control and lipid concentrations in patients with gestational diabetes. J Clin Lipidol. 2017; 11:459–68. https://doi.org/10.1016/j.jacl.2017.01.011 • Li Q, Xing B. Vitamin D3-Supplemented Yogurt Drink Improves Insulin Resistance and Lipid Profiles in Women with Gestational Diabetes Mellitus: A Randomized Double Blinded Clinical Trial. Ann Nutr Metab. 2016; 68:285–90. https://doi.org/10.1159/000447433 • Karamali M, Bahramimoghadam S, Sharifzadeh F, Asemi Z. Magnesium–zinc–calcium–vitamin D co-supplementation improves glycemic control and markers of cardiometabolic risk in gestational diabetes: a randomized, double-blind, placebo-controlled trial. Appl Physiol Nutr Metab. 2018; 43:565–70. Available from: http://www.nrcresearchpress.com/doi/10.1139/apnm-2017-0521 • Hosseinzadeh-Shamsi-Anar M, Mozaffari-Khosravi H, Salami M-A, Hadinedoushan H, Mozayan MR. The efficacy and safety of a high dose of vitamin d in mothers with gestational diabetes mellitus: a randomized controlled clinical trial. Iran J Med Sci. 2012; 37:159–65. Available from: http://www.ncbi.nlm.nih.gov/pubmed/23115447 • Saha S. Impact of missingness on clinical trials on the effectiveness of antenatal vitamin D supplementation in gestational diabetes mellitus patients. J Ideas Heal. 2020; 3:138–9. https://doi.org/10.47108/jidhealth.Vol3.Iss1.47 • Saha S, Saha S. The variation in participant attrition between prenatal vitamin D supplemented and not supplemented gestational diabetes mellitus patients: a systematic review and meta-analysis of randomized controlled trials. PROSPERO. 2020. https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020180634 • Moher D, Shamseer L, Clarke M, Ghersi D, Liberati A, Petticrew M, et al. Preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) 2015 statement. Syst Rev. 2015; 4:1. https://doi.org/10.1186/2046-4053-4-1 • Ouzzani M, Hammady H, Fedorowicz Z, Elmagarmid A. Rayyan—a web and mobile app for systematic reviews. Syst Rev. 2016; 5:210. https://doi.org/10.1186/s13643-016-0384-4 • American Diabetes Association. Diagnosis and classification of diabetes mellitus. Diabetes Care. 2014;37 Suppl 1: S81-90. https://doi.org/10.2337/dc14-s081 • Rossi G, American Diabetes Association. [Diagnosis and classification of diabetes mellitus]. Recenti Prog Med. 2010; 101:274–6. http://www.ncbi.nlm.nih.gov/pubmed/20842952 • Nyaga VN, Arbyn M, Aerts M. Metaprop: a Stata command to perform meta-analysis of binomial data. Arch Public Heal. 2014; 72:39. http://archpublichealth.biomedcentral.com/articles/10.1186/2049-3258-72-39 • Higgins JPT, Thompson SG, Deeks JJ, Altman DG. Measuring inconsistency in meta-analyses. BMJ. 2003; 327:557–60. http://www.bmj.com/cgi/doi/10.1136/bmj.327.7414.557 • Atkins D, Best D, Briss PA, Eccles M, Falck-Ytter Y, Flottorp S, et al. Grading quality of evidence and strength of recommendations. BMJ. 2004; 328:1490. http://www.bmj.com/lookup/doi/10.1136/bmj.328.7454.1490 • Liberati A, Altman DG, Tetzlaff J, Mulrow C, Gøtzsche PC, Ioannidis JPA, et al. The PRISMA statement for reporting systematic reviews and meta-analyses of studies that evaluate health care interventions: explanation and elaboration. J Clin Epidemiol.2009;62: e1–34. https://doi.org/10.1016/j.jclinepi.2009.06.006